Implementation of the Spectral Method for Determining of Measuring Instruments' Dynamic Characteristics - A. F. Sabitov; I. A. Safina (Приборы и методы измерений)
The spectral method for establishing dynamic response of measuring instruments basically requires determining the amplitude spectrum of the signal in its informative part that includes the amplitude spectrum at zero frequency. The operating frequency range of existing low-frequency spectrum analyzers is above zero frequency that leads to an uncertainty in dynamic response of measuring instruments determined by the spectral method. The purpose of this paper is to develop a program for calculating the signal amplitude spectrum, starting from zero frequency, to implement a spectral method for determining the dynamic response of measuring instruments on computers equipped with the MatLab package.To implement the spectral method for determining the dynamic response of measuring instruments, we developed a program in the MatLab 2013b environment that determines the signal amplitude spectrum from zero Hertz. The program reads the source data from Excel tables and presents the calculated amplitude spectrum as a chart and a report table.It is shown that the developed program calculates the signal amplitude spectrum with a standard deviation of not more than 3.4 % in the frequency range of 0 to 10 rad/s. The calculated amplitude spectrum allows determining the time constant of first-order aperiodic measuring instruments with an uncertainty of not more than 0.166 % at any noise level, if their frequencies are outside the information part of the spectrum.We demonstrated the claimed advantage of the spectral method for determining dynamic response using the developed program by the example of a high-frequency noise in the transient response of some measuring instruments.